Spatiotemporal variations of T/ET (the ratio of transpiration to evapotranspiration) in three forests of Eastern China. (May 2015) - Zhu, Xian-Jin; Yu, Gui-Rui; Hu, Zhong-Min; Wang, Qiu-Feng; He, Hong-Lin; Yan, Jun-Hua; Wang, Hui-Min; Zhang, Jun-Hui
Highlights: Run the Shuttleworth–Wallace model and validated its performance in forest ecosystems. Transpiration occupied over 60% of evapotranspiration in three forests of Eastern China. Canopy stomal conductance dominated the spatiotemporal variations of forest T /ET. S wc also affected the seasonal variation of T /ET in subtropical forest through G s . Abstract: Evapotranspiration (ET), which is comprised by evaporation from soil surface ( E ), transpiration ( T ) and evaporation from the intercepted water by canopy (EI), plays an important role in maintaining global energy balance and regulating climate. Quantifying the spatiotemporal variations of T /ET (the ratio of T to ET) can improve our understandings on the role of vegetation ecophysiological processes in climate regulation. Using eddy covariance measurements at three forest ecosystems (Changbaishan temperate broad-leaved Korean pine mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ) and Dinghushan subtropical evergreen mixed forest (DHS)) in north–south transect of Eastern China (NSTEC), we run the revised Shuttleworth–Wallace model (S–W model), validated its performance with the water vapor fluxes measured at two layers, and quantified the spatiotemporal variations of T /ET. The S–W model performed well in simulating ET and T /ET. The mean value of annual T /ET at three forests during the observation period all exceeded 0.6. The diurnal variation of canopy stomal conductance ( G c ) dominated that of T /ET. The seasonal dynamics of T /ET was mainly shaped by that of leaf area index (LAI), vapor pressure deficit (VPD) and air temperature ( T a ) through altering G c and the portion that the energy absorbed by canopy ( P EC ) at temperate forest (CBS), while the seasonal dynamics of T /ET at subtropical forests (QYZ and DHS) were mainly affected by T a, net radiation, VPD, and soil water content through altering G c and soil surface conductance ( G s ). The variation of mean annual G c governed the interannual varaition and spatial variation of T /ET. Therefore, forests in Eastern China played an important role in regulating climate through T and G c primarily affected the spatial and temproal variations of the role of forest T in regulating climate.